Stenting as a bridge to surgery for extra-colonic malignancy induced colorectal obstruction: preliminary experience - Eui Joo Kim (BMC Gastroenterology, 2020)
Abstract Background The majority of colonic obstructions result from colorectal cancer. However, malignancies of extra-colonic origin can also disrupt colorectal patency, and the efficacy of self-expanding metal stents (SEMS) insertion as a bridge to surgery in these patients are still in debate. The aim of this study is to evaluate the efficacy of endoscopic stenting as a bridge to surgery (BTS) for extra-colonic malignancy (ECM)-induced colonic obstruction. Methods Thirty-three patients with colonic obstruction due to ECM who received self-expanding metal stents (SEMS) insertion at a single academic tertiary medical center between 2004 and 2015 were included. The purpose of SEMS insertion was determined based on whether the patient’s medical records indicated any surgical plans before SEMS insertion. Technical success was defined as a patent SEMS covering the entire length of the obstruction. Bridging success was defined as elective surgical procedures after the first SEMS insertion. Results Among the 33 patients who underwent SEMS insertion for colorectal obstruction due to ECM, nine underwent SEMS as a BTS. Technical success was achieved in 100% (9/9). Seven patients underwent elective surgery after successful decompression with the first SEMS, and the bridging success rate was 77.8% (7/9). Two patients needed secondary stent insertion before elective surgery. However, none of them required emergent surgery. No major complications occurred, including death related to colorectal endoscopic procedures, perforation, or bleeding. Conclusion SEMS insertion as a BTS is a good treatment option to avoid emergent surgery in patients with colonic obstruction caused by extra-colonic malignancy.